Growth and production of cowpea BRS Tumucumaque cultivated in different population densities (Research, Society and Development, 2021)
Cowpea is an excellent protein source of vegetable origin with high nutritional value, very important in the North, Northeast and Midwest regions of Brazil. Sowing density can influence the agromorphological characters of crops, especially grain yield.The objective of this work was to evaluate the influence of different population densities on the growth and production of the cultivar BRS-Tumucumaque. The experiment was conducted in the Chapada Gaúcha-MG city, between February and May 2019. The experimental design was a randomized block (DBC), with 4 replications, composed of 5 population densities (100.000, 150.000, 200.000, 250.000 and 300.000 plants ha-1) in 0.5 m spacing. Growth was evaluated by plant height (AP), stalk diameter (DC) and number of pods per plant (NVP). Yield was evaluated by the number of grains per pod (NGV), one hundred grain mass (M100G) and yield (PROD). Only productivity was influenced in a linear and positive way by the variation in population density. The population increase from 100 to 300 thousand plants ha-1 resulted in a total increase of 33.5% in grain yield, equivalent to 1,523.46 kg ha-1.